2018
DOI: 10.1245/s10434-018-6634-z
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Tumor Markers Independently Predict Survival in Stage III Gastric Cancer Patients: Should We Include Tumor Markers in AJCC Staging?

Abstract: Preoperative CEA/CA19-9 levels are an independent predictor of OS and DSS in stage III GC patients. The inclusion of preoperative CEA/CA19-9 levels in AJCC TNM staging provided an optimal prognosis in stage III GC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…It is suggested that serum tumour markers could be used in clinical practice as an additional tool for screening, tumour staging, prediction of prognosis and even surveillance of treatment in several cancer types (Zhang et al 2007, Adamo et al 2017, Lin et al 2018. Carcinoembryonic antigen (CEA) and carbohydrate antigen 19-9 (CA19-9) are the most studied serum biomarkers for establishing both diagnosis and prognosis in pancreatic cancer patients (Goonetilleke andSiriwardena 2007, Meng et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that serum tumour markers could be used in clinical practice as an additional tool for screening, tumour staging, prediction of prognosis and even surveillance of treatment in several cancer types (Zhang et al 2007, Adamo et al 2017, Lin et al 2018. Carcinoembryonic antigen (CEA) and carbohydrate antigen 19-9 (CA19-9) are the most studied serum biomarkers for establishing both diagnosis and prognosis in pancreatic cancer patients (Goonetilleke andSiriwardena 2007, Meng et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Whether serum CA19-9 levels should be used as prognostic indicators in patients with gastric cancer has long been discussed; however, the results remain controversial. Some studies reported that CA19-9 level was an independent prognostic factor by multivariate analysis in gastric cancer; gastric cancer patients with elevated CA19-9 levels had poorer prognosis than those with normal CA19-9 (13,14,16,26). However, other studies showed than preoperative CA19-9 levels were not an independent prognostic factor in gastric cancer (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…5 Both NLR and PLR inflammation markers have demonstrated prognostic values in previous studies. 19 , 20 In the present study, we evaluated the new nomogram model for prognosis prediction in stage III CRC patients. We found that both PLR and NLR were independent prognostic factors affecting lymph node metastasis in CRC.…”
Section: Discussionmentioning
confidence: 99%